The institutional scholarship program for teaching - pibid: an analysis of the thematic projects 2016 and 2017 subproject geography of ufpe - Sousa, Laryssa de Aragão; Santos, Francisco Kennedy Silva dos; Carvalho, Josias Ivanildo Flores de (Geosaberes, 2018)
This work aims to contribute to a critical analysis of the projects of PIBID Geography of UFPE, a temporal cut during the years 2016 and 2017 and the impact from the importance of pedagogical projects as a whole. Specifically, the thematic projects "Social Cartography and School" and "Leisure activities in the teaching of Geography" under the training and didactic action of the Pibidians, specifically the Pibidians of Geography of UFPE who work with the experiential method.The methodology of this research follows a qualitative approach, and was done through documentary analysis, literature review and interviews of the Pibidians, subjects participating in the projects of the years 2016 and 2017.